Biopharmaceutical substantiation of the solvent in the composition of the immunobiological drug for prevention and treatment of candidal infection - Rybalkin, М; Strilets, O; Strelnikov, L; Kalyuzhna, O (Annals of Mechnikov's Institute, 2020)
Today diseases caused by potentially pathogenic microorganisms become increasingly important. This phenomenon is connected with increase of power of influence of the environment: chemical pollution, radiation, irrational use of antibiotics and hormone therapy; it leads to decrease of the immune response and human nonspecific resistance. For the last years one of the indicators of failure of the human body immune protection is chronic and local candidiases caused by potentially pathogenic fungi of Candida genus. Prevalence and risk of candidal infections determine the need for searching new medicines with a high efficiency and safety for human. Development of a vaccine for prevention and treatment of candidal infection is being actively conducted in many countries of the world. It should be noted that currently no domestic vaccine is produced in Ukraine and no candidiasis vaccines have been registered. Therefore, development of such vaccine is the topical issue of modern pharmacy and medicine. In our previous studies it was found that the immunobiological drug based on the antigens of fungi of C. albicans with the protein concentration of 3 mg/ml and C. tropicalis with the protein concentration of 5 mg/ml in the ratio of 1:1 possesses the protective and therapeutic effect. At the current stage of research it is necessary to substantiate the solvent in the composition of the immunobiological drug. The aim of this work is the experimental substantiation of the solvent in the composition of the immunobiological drug based on the antigens of C. albicans and C. tropicalis fungi. Materials and Methods. The immunobiological drug with the protein concentration of 4 mg/ml was investigated using various solvents. The following solvents was studied: water for injections, 0.9 % isotonic saline solution, phosphate buffer solution. To determine the protective and therapeutic activity of the immunobiological drug based on the antigens of C. albicans and C. tropicalis fungi the research was conducted in healthy two-month white mice with the body weight of 18-22 g. There were 6 animals in the control and test groups. Mice were intramuscularly injected 0.2 ml of the immunobiological drug twice with an interval of 14 days. To determine the protective activity of the immunobiological drug the animals were infected intraperitoneally in 3 months after the second introduction. For this purpose the suspension of Candida albicans fungi of ССМ 335-867 strain in the amount of 20 mln. of cells and Candida tropicalis of АТТС 20336 strain in the amount of 60 mln. of cells in the volume of 1 ml was used; they were introduced with the interval of 1 hour. After that in 14 days the animals were examined and the results were determined. To determine therapeutic activity of the immunobiological drug the animals were infected according to the scheme described, in 5 days a doulble injection of the drug was introduced to mice. After that in 14 days the animals were examined and the results were determined. As a result of the research conducted it was found that the immunobiological drug based on the antigens of C. albicans and C. tropicalis fungi with all solvents studied protected 100 % of animals from infection in 1 and 3 months. The therapeutic effect of the immunobiological drug based on the antigens of C. albicans and C. tropicalis fungi with all solvents was 100 %. The therapeutic effect started to exhibit in 8 - 14 days after the first introduction of the vaccine, and in 8 - 14 days after the repeated introduction of the vaccine the full recovery of animals occurred. In animals of the control group the signs of infection corresponding to the moderate form of the disease and the advanced form of the disease were registered. Taking into account the fact that the immunobiological drug with all solvents has shown the similar results the use of phosphate buffer solution is more expedient for further study because it preserves the constant value of the рН medium for a long period of time. Thus, it provides the drug stability since an insignificant change in рН can greatly affect the activity of antigens, and it will have an influence on the drug activity.